Bullying and victimisation are common in four‐year‐old children and are associated with somatic symptoms and conduct and peer problems. (2nd February 2016) - Ilola, Anna‐Marja; Lempinen, Lotta; Huttunen, Jukka; Ristkari, Terja; Sourander, Andre
Abstract: Aim: There are few population‐based studies on bullying behaviour among preschool children. The aims of the study were to investigate the prevalence of bullying behaviour among four‐year‐old children, as reported by their parents, the prevalence of types of bullying behaviour and the associations between bullying behaviour and psychosocial factors. Methods: This study was based on a population‐based study sample of 931 children who attended their check‐up at a child health clinic at four years of age. Parents completed the questionnaire about their child's bullying behaviour and risk factors during the check‐up. Results: Bullying behaviour, especially being both a bully and a victim, was a common phenomenon among four‐year‐old children. Being a bully or both a bully and victim were most strongly associated with conduct problems, while being a victim was associated with somatic symptoms and peer problems. Conclusion: Bullying behaviour was frequently found in preschool children and associated with a wide range of other problems, which indicate that routine checking of bullying behaviour should be included in child health clinic check‐ups. Bullying prevention programmes are usually targeted at school‐aged children, but this study highlights the importance of focusing already on preschool children.